Assessment of lingual nerve injury using different surgical variables for mandibular third molar surgery: a clinical study - Yadav, S.; Verma, A.; Sachdeva, A. (International journal of oral and maxillofacial surgery, 2014)
The objective of this study was to investigate the incidence of sensory impairment of the lingual nerves following lower third molar removal and to compare the outcome with various operative variables. A total of 1200 mandibular third molars were removed under local anaesthesia. Predictor variables were categorized as lingual flap retraction, tooth sectioning, and buccal guttering. The outcome variable was the presence or absence of lingual nerve impairment. Different operative techniques were performed to identify independent predictors. Of the 1200 patients, 67 (5.6%) experienced transient sensory impairment at the 1-week follow-up. In all cases this resolved completely during the study period, except for four (0.3%) patients who suffered permanent impairment of lingual nerve function. Factors that predicted lingual nerve injury were lingual flap retraction, tooth sectioning, and buccal guttering. The incidence of lingual nerve injury was greater when combinations of these operative variables were used.